Bachelard, a present: au coeur de l’oeuvre de Giuseppe Penone (Altre Modernità, 2012)
The perennial relevance of Bachelard’s poetic insight makes him a prophet for an age of ecological alienation. He clarifies the intuition of visual artists "since the 1960's", exemplified in the art of Giuseppe Penone, and their common “volonté de regarder à l’intérieur des choses.” How then does an artist such as Penone go from inside real things to arrive at this “intimité des substances” (Bachelard 1948 : 5). How do both men aspire to “l’immensité intime”?